Nutrient foramen location on the laminae provides a landmark for pedicle screw entry: a cadaveric study - Oshina, Masahito (BMC Musculoskelet Disord, 2018)
BACKGROUND: Nutrient foramina are often encountered around the entry point of pedicle screws. Further, while probing the pedicle for pedicle screw insertion around the nutrient foramen, bleeding from the probe insertion hole is often observed. The purpose of this study was to investigate the frequency of occurrence of nutrient foramina, the association between the nutrient foramen and pedicle, and the safety and accuracy of cervical and thoracic pedicle screw placement using the nutrient foramen as the entry point. METHODS: We identified the location of the nutrient foramina for the dorsal branches of the segmental artery and their anatomical association to the pedicles and bony landmarks in the vertebrae for C3–T12 in seven cadavers. We also determined the frequency with which the nutrient foramina were present in 119 cadaveric vertebrae. We identified the pedicle location, base of the superior articular facet, and lateral border of laminae with respect to the nutrient foramen. RESULTS: The overall presence of the nutrient foramina was 63% (150/238) in the specimens, with 60% (42/70) and 64% (108/168) identifiable in the cervical and thoracic vertebrae, respectively. In the cervical vertebrae, the nutrient foramen was located on the outer wall of the pedicle and was positioned between the cephalad and caudal walls. In the thoracic spine, 98% (106/108) nutrient foramina were located inside the pedicle walls. CONCLUSIONS: Our study findings confirm that the location of the nutrient foramen can be used for identifying the entry point for pedicle screws. In the cervical vertebrae, the nutrient foramina are located lateral to pedicle but within the cranial and caudal margins. In the thoracic vertebrae, the nutrient foramina are located in the medial and caudal regions of the pedicle. Thus, to decrease the risk of overshoot, the entry point for thoracic pedicle screws should be positioned a few millimeters cephalad and lateral to the nutrient foramen.